31P magnetic resonance spectroscopy in dilated cardiomyopathy and coronary artery disease: Altered cardiac high-energy phosphate metabolism in heart failure - Neubauer, S; Krahe, T; Schindler, R; Horn, M; Hillenbrand, H; Entzeroth, C; Mader, H; Kromer, E; Riegger, G; Lackner, K; Ertl, G (1992)
Background. The purpose of this work was to further define the value of cardiac 31P magnetic resonance (MR) spectroscopy for patients with coronary artery disease and dilated cardiomyopathy. Methods and Results. Blood-corrected and 31T1-corrected 31P MR spectra of anteroseptal myocardium were obtained at rest using image-selected in vivo spectroscopy localization, a selected volume of 85±12 cm3, and a field strength of 1.5 T. Nineteen volunteers had a creatine phosphate (CP)/ATP ratio of 1.95±0.45 (mean±SD) and a PDE/ATP ratio of 1.06±0.53; in four patients with left anterior descending coronary artery (LAD) stenosis, six patients with chronic anterior wall infarction, and four patients with chronic posterior wall infarction, CP/ATP and phosphodiester (PDE)/ATP ratios did not differ from those in volunteers. Twenty-five measurements of 19 patients with dilated cardiomyopathy yielded a CP/ATP of 1.78±0.51 and a PDE/ATP of 0.98±0.56 (p=NS versus volunteers). When these patients were grouped according to the severity of heart failure, however, CP/ATP was 1.94±0.43 in mild (p=NS versus volunteers) and 1.44±0.52 in severe DCM (p<0.05), respectively. No correlation was found between CP/ATP and left ventricular ejection fraction or fractional shortening, but correlation of CP/ATP with the New York Heart Association (NYHA) class was significant (r=0.60, p<0.005). Six patients with dilated cardiomyopathy were studied repeatedly before and after 12±6 weeks of drug treatment leading to clinical recompensation with improvement of the NYHA status by 0.8±0.3 classes. Concomitantly, CP/ATP increased from 1.51±0.32 to 2.15±0.27 (p<0.01), whereas PDE/ATP did not change significantly. Conclusions. Cardiac high-energy phosphate metabolism at rest is normal in LAD stenosis and chronic myocardial infarction in the absence of heart failure. The CP/ATP ratio has low specificity for the diagnosis of dilated cardiomyopathy. However, CP/ATP correlated with the clinical severity of heart failure and may improve during clinical recompensation.